Digestion‐Promoting Effects and Mechanisms of Dashanzha Pill Based on Raw and Charred Crataegi Fructus. Issue 12 (16th November 2021) - Liu, Cui; He, Qian; Zeng, Linlin; Shen, Ling; Luo, Qiaomei; Zhang, Wentao; Zhou, Xia; Wan, Jun
Abstract: Emerging evidence suggests that a high‐fat diet (HFD) can influence endoplasmic reticulum (ER) stress and gut microbiota. Crataegi Fructus is a traditional Chinese herb widely used in formulas for dyspepsia, with Dashanzha Pill composed of raw Crataegi Fructus (DR) being a representative drug. Processing products of Crataegi Fructus, however, have a stronger pro‐digestive effect, and we hypothesized that Dashanzha Pill composed of charred Crataegi Fructus (DC) is more effective. We found that the contents of glucose 1‐phosphate and luteolin in DR and DC were substantially different via ultra‐high performance liquid chromatography‐hybrid quadrupole‐Orbitrap high‐resolution mass spectrometry. DC outperformed DR in improving histopathological changes, increasing gastrin and motilin, and decreasing vasoactive intestinal peptides in rats with HFD induced dyspepsia. Fecal microbiota analysis revealed that DC could restore the disturbed intestinal microbiota composition, including that of Bacteroides, Akkermansia, and Intestinimonas to normal levels. Furthermore, DC significantly reduced the mRNA and protein levels of glucose‐regulated protein 78, protein kinase R‐like ER kinase, and eukaryotic initiation factor 2α. Taken together, DC outperformed DR in relieving dyspepsia by regulating gut microbiota and alleviating ER stress. Abstract :